Urban poverty and nutrition challenges associated with accessibility to a healthy diet: a global systematic literature review - Vilar-Compte, Mireya; Burrola-Méndez, Soraya; Lozano-Marrufo, Annel; Ferré-Eguiluz, Isabel; Flores, Diana; Gaitán-Rossi, Pablo; Teruel, Graciela; Pérez-Escamilla, Rafael (International journal for equity in health, 2021)
Background There is an increasing global trend towards urbanization. In general, there are less food access issues in urban than rural areas, but this “urban advantage” does not benefit the poorest who face disproportionate barriers to accessing healthy food and have an increased risk of malnutrition. Objectives This systematic literature review aimed to assess urban poverty as a determinant of access to a healthy diet, and to examine the contribution of urban poverty to the nutritional status of individuals. Methods Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) methodology, our review included quantitative and qualitative studies published in English or in Spanish between 2000 and 2019. The articles were eligible if they focused on nutrition access (i.e. access to a healthy diet) or nutrition outcomes (i.e., anemia, overweight and obesity, micronutrient deficiency, micronutrient malnutrition) among urban poor populations. Articles were excluded if they did not meet pre-established criteria. The quality of the quantitative studies was assessed by applying Khan et al.’s methodology. Similarly, we assessed the quality of qualitative articles through an adapted version of the National Institute for Health and Care Excellence (NICE) methodology checklist. Finally, we systematically analyzed all papers that met the inclusion criteria based on a qualitative content and thematic analysis. Results Of the 68 papers included in the systematic review, 55 used quantitative and 13 used qualitative methods. Through the analysis of the literature we found four key themes: (i) elements that affect access to healthy eating in individuals in urban poverty, (ii) food insecurity and urban poverty, (iii) risk factors for the nutritional status of urban poor and (iv) coping strategies to limited access to food. Based on the systematization of the literature on these themes, we then proposed a conceptual framework of urban poverty and nutrition. Conclusions This systematic review identified distinct barriers posed by urban poverty in accessing healthy diets and its association with poorer nutrition outcomes, hence, questioning the “urban advantage”. A conceptual framework emerging from the existing literature is proposed to guide future studies and policies. Systematic review registration PROSPERO Registration number: CRD42018089788 .